Hybrid nanomaterial inks for printed resistive temperature sensors with tunable properties to maximize sensitivity. Issue 1 (8th December 2022) - Tursunniyaz, Muhammadeziz; Agarwal, Vasvi; Meredith, Anna; Andrews, Joseph
Abstract : Flexible resistive temperature sensors with tunable temperature coefficient of resistance and sensitivity fabricated by aerosol jet printing with hybrid nanomaterial inks. Abstract : Nanomaterial-based inks are one of the essential building blocks for printed electronics. Inks consisting of silver nanoparticles have been well received as conductive inks for printed electronics among researchers and industry due to their good electrical performance, relatively low sintering temperature, and wide range of commercial availability. However, homogenous silver nanoparticle inks can lack the appropriate attributes required for robust printed physical sensors. In this work, we demonstrate that fully printed resistive temperature detector (RTD) sensors can benefit from ink hybridization. Specifically, we investigate RTDs printed by aerosol jet printing of hybrid nickel–copper-silver nanoparticle inks. We show that the overall sensitivity of the printed sensors can be enhanced through the introduction of these varied particles due to intentionally incorporated interfacial obstacles within the percolation network. While the temperature coefficient of resistance is decreased, the change in resistance per change in temperature can be maximized through the enhanced scattering provided by nickel and copper particle constituents. We report a sensitivity increase of 300% through utilizing 40% (by volume) mixture of silver and copper/nickel xylene-based inks. The results are corroborated through SEM/EDS analysis to understand the final weight percent of varied elements within the printed thin film. This magnitude of sensitivity opens up the possibility of utilizing printed RTDs for a wider range of sensing applications, where probing electronics are often low-cost.